2022
DOI: 10.3389/fchem.2022.886367
|View full text |Cite
|
Sign up to set email alerts
|

From Biomass-Derived p-Hydroxycinnamic Acids to Novel Sustainable and Non-Toxic Phenolics-Based UV-Filters: A Multidisciplinary Journey

Abstract: Although organic UV-filters are extensively used in cosmetics to protect consumers from the deleterious effects of solar UV radiation-exposure, they suffer from some major drawbacks such as their fossil origin and their toxicity to both humans and the environment. Thus, finding sustainable and non-toxic UV-filters is becoming a topic of great interest for the cosmetic industry. A few years ago, sinapoyl malate was shown to be a powerful naturally occurring UV-filter. Building on these findings, we decided to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…Rapid internal conversion to the ground electronic state then releases the energy as heat. The part of the solar spectrum not used for photosynthesis can thus be employed to raise crop temperatures and boost crop yields. , Facile excited-state cis–trans isomerization drives the fast internal conversion, effectively providing efficient UV-to-heat conversion pathways. , DGSM has two lipophilic tails that enable the molecule to stick to the wax layer of leaves, making it resistant to rainwater wash-off. However, this feature also raises concerns regarding intake through consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid internal conversion to the ground electronic state then releases the energy as heat. The part of the solar spectrum not used for photosynthesis can thus be employed to raise crop temperatures and boost crop yields. , Facile excited-state cis–trans isomerization drives the fast internal conversion, effectively providing efficient UV-to-heat conversion pathways. , DGSM has two lipophilic tails that enable the molecule to stick to the wax layer of leaves, making it resistant to rainwater wash-off. However, this feature also raises concerns regarding intake through consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid is present in non-neglectable quantities in some agricultural byproducts and has been proven to have antimicrobial and antioxidant properties. Several studies have shown that ferulic acid-derivatives can exhibit both aforementioned activities, as well as UV-filtering properties. In addition, endocrine disrupting tests conducted on ferulic acid derivatives have proven negative . All of these advantages make ferulic acid the perfect synthon for the design of multifunctional ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…20−22 In addition, endocrine disrupting tests conducted on ferulic acid derivatives have proven negative. 23 All of these advantages make ferulic acid the perfect synthon for the design of multifunctional ingredients.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, compared to donepezil, Contilisant has superior in vivo protective effects in Y-maze and radial-arm maze against cognitive decline induced by the β -amyloid peptide A β 1–42 oligomers [ 17 ]. On the other hand, unlike petroleum-based molecules, natural products such as ferulic acid (FA) ( Figure 1 ) are biologically derived and sustainable substances that are preferred in the chemical and pharmaceutical industries [ 18 , 19 ]. Moreover, they have shown promising pharmacological effects that could be useful for the treatment of AD, such as antioxidant effects, neuroprotection, and promotion of neurogenesis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%